GAYA RETORIKA BAGIAN METODOLOGI PENELITIAN PADA JURNAL NASIONAL TERAKREDITASI BIDANG SOSIAL DAN HUMANIORA - suryadi, suryadi; arono, arono (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The research methodology section in a journal article is one of the most important things in determining the accuracy of the results of the research conducted by the author. However, in reality it is different from the scientific study that is written, the stages will be different in the journal article in which the article is published. The purpose of this study is to find the rhetorical style of the research methodology section in accredited social and humanitarian national journals by not discussing the linguistic aspects in it. This study used descriptive qualitative method. The data collection techniques are grouping knowledge based on sinta accreditation, analyzing the data, determining proportional journal articles, and determining journal articles. Data analysis techniques, namely journal articles that have been determined to be tabulated in the methodology section, transcribe the contents of the research methodology section, tabulate based on linguistic stages and aspects, interpret, and draw conclusions. Validity is done by checking with a team of three experts. This study describes the rhetorical style of the research methodology section of an accredited national journal in the social and humanitarian field by not discussing the linguistic aspects in it. The results of the study indicate that working in the social and humanities fields accredited journal articles in the research methodology section in the social and humanities field are. move the research method which contains a research component method, the research subject section has a research object section, the research procedure section contains component procedures, and the analysis section contains a data analysis component. The linguistic features contained in the methodology section in this study, namely, are, and, namely, with, in, as well as, for, because, and so. This linguistic feature shows that the methodology section of this study presents explanatory and argumentative sentences using complex sentences, both equivalent compound sentences and mixed compound sentences.